Does Measurement Error Explain the Increase in Subminimum Wage Payment Following Minimum Wage Increases? - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2022)
In analyses of minimum wages, positive "ripple effects" and subminimum wages are difficult to distinguish from measurement error. Indeed, prior work posits that a simple, symmetric measurement process may underlie both phenomena in Current Population Survey data for the full working age population. We show that the population-wide symmetry between spillovers and subminimum wage payment is illusory in that spillovers accrue to older individuals while underpayment accrues to the young. Symmetric measurement error cannot explain this heterogeneity, which increases the likelihood that both spillovers and subminimum-wage payment are real effects of minimum wage increases rather than artifacts of measurement error.
Keywords: J08; J38; K42; 330; minimum wage; subminimum wage; noncompliance